Synthesis of Optimal Dynamic Mode of Manipulator Boom Movement Mounted on Elastic Base - V. S. Loveikin; D. A. Mischuk (Наука и техника)
In order to increase reliability and accuracy of robot manipulators or other construction equipment used for lifting operations an optimum dynamic mode for moving its boom system has been calculated in the paper. Results of the research have made it possible to construct a mathematical model for manipulator movement and obtain kinematic characteristics of the optimum dynamic mode. While determining the optimum dynamic motion mode, a criterion action has been used as an optimization criterion which represents a time integral with an integrand function expressing a dynamic component of manipulator drive power. Functions for changing kinematic characteristics of an manipulator boom have been calculated when it moves from one predetermined position to another one and which correspond to optimum dynamic mode of motion. Search for an optimum motion mode has been performed by minimizing the optimization criterion using the Euler–Poisson equations. In this case a generalized angle of rotation has been used which permits to relate movement of the boom and oscillations of its support part. As a linking component differential equations of system motion have been also applied, in which relationships between an oscillation angle, rigidity of a manipulator support, and its mass-geometric characteristics have been recorded. Results of the work can be useful for refinement and improvement of existing engineering methods for calculating the drive mechanisms of manipulators both at design/construction stages and in real operation modes, and the results can also be used while making design or improvement of similar executive mechanisms for construction equipment and robots.